Healthy, regenerative and just: Guiding the development of a national strategy on climate, health and well-being for Australia - Fiona Armstrong; Arthur Wyns; Philomena Colagiuri; Rory Anderson; Arnagretta Hunter; Kerry Arabena; Colin Russo; Steven Cork; Serena Joyner; Mark Howden; Melissa Haswell; Tarun Weeramanthri; et al. (The Journal of Climate Change and Health, 2023)
This case report is a reflective narrative, documenting the methods used to develop a policy framework for a National Strategy on Climate, Health and Well-being for Australia. The report aims to guide advocates, communities of practice, and governments in developing a comprehensive policy response to climate change and its health impacts.